2020
DOI: 10.1186/s13578-020-00477-1
|View full text |Cite
|
Sign up to set email alerts
|

Phloretin ameliorates hepatic steatosis through regulation of lipogenesis and Sirt1/AMPK signaling in obese mice

Abstract: Background Phloretin is isolated from apple trees and could increase lipolysis in 3T3-L1 adipocytes. Previous studies have found that phloretin could prevent obesity in mice. In this study, we investigated whether phloretin ameliorates non-alcoholic fatty liver disease (NAFLD) in high-fat diet (HFD)-induced obese mice, and evaluated the regulation of lipid metabolism in hepatocytes. Methods HepG2 cells were treated with 0.5 mM oleic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 48 publications
(73 reference statements)
2
13
0
Order By: Relevance
“…In the liver of these animals, phloretin inhibited lipogenesis and promoted lipolysis. Furthermore, in HepG2 cells (a human liver cancer cell line) induced with oleic acid to accumulate fat, treatment with phloretin decreased the accumulation of lipid droplets and inhibited the expression of lipogenesis-related transcription factors [37]. Similar results have also been obtained in a study with mice treated with a high-fat diet supplemented or not with phloretin.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…In the liver of these animals, phloretin inhibited lipogenesis and promoted lipolysis. Furthermore, in HepG2 cells (a human liver cancer cell line) induced with oleic acid to accumulate fat, treatment with phloretin decreased the accumulation of lipid droplets and inhibited the expression of lipogenesis-related transcription factors [37]. Similar results have also been obtained in a study with mice treated with a high-fat diet supplemented or not with phloretin.…”
Section: Discussionsupporting
confidence: 70%
“…Therefore, phloretin could act mainly in stages of adipogenesis with higher metabolic activity, favoring in part lipolysis. This has been observed in experimental models using such flavonoids, like the liver of obese mice [37] and in 3T3-L1 cells differentiated into adipocytes [35]. In addition, activation of the Wnt/β-catenin pathway has also been associated with increased lipolysis [73].…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Some studies have suggested that maternal obesity is related to the onset of NAFLD in the offspring and the oxidation of their lipids ( 6 , 7 ). Previous articles have commonly used male rats that were fed a high-fat diet to establish NAFLD models ( 8 , 9 ). Borengasser et al ( 10 ) induced obesity in female Spring Dawley rats (SD) via a high fat diet.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that Sirt1 upregulates the expression of phosphorylated AMPK under exposure to diabetic conditions ( Karbasforooshan and Karimi, 2018 ). The Sirt1/AMPK pathway can participate in hepatic steatosis in obese mice ( Liou et al, 2020 ). Our results indicate that treatment of the NAD substrate with NR increased the expression of phosphorylated AMPK in diabetic EPCs.…”
Section: Discussionmentioning
confidence: 99%